If the average of three numbers is V if one number is Z and another is y what is the remaining number ?

Answers

Answer 1
Answer:

The remaining number, using the concept of average, is  3V-y-z

It is given that

Average of three numbers = V

One number  = z

Another number = y

What is an average?

Average is the sum of observations divided by a number of observations.

Let us take the third number  x

From the question

(x+y+z)/(3) = V

x+y+z = 3V\n\nx=3V-y-z

Therefore, the remaining number is 3V-y-z

To get more about the average visit:

brainly.com/question/6504879

Answer 2
Answer: The formula for an average of three numbers is (x+y+z)/3.  So if V equals the average, then we find the formula
V = (x+y+z)/3
We are now looking for x.  We can divide each of the variables in the parentheses by 3, making the formula
V = x/3 + y/3 + z/3
So now bring the unwanted variables to the same side as V.
V - y/3 - z/3 = x/3
Now multiply both sides by 3 to find x.
3V - y - z = x

x = 3V - y - z

Related Questions

Find the product of (4x + 3y)(4x − 3y).16x2 − 24xy + 9y2 16x2 − 9y2 16x2 + 24xy + 9y2 16x2 + 9y2
What is the factored form of the polynomial? x2 - 15x + 36
Sammy has $0.37 in his pocket he only has four coins.What coins does he have in his pockets??
Which conversion requires division
A number increased by four is the same as 19 minus 2 times the number

Isiah determined that 5a2 is the GCF of the polynomiala3 – 25a2b5 – 35b4. Is he correct? Explain.

Answers

Answer:

No, Isiah is not correct. The GCF of the coefficients is 1, and there are no common variables among all three terms of the polynomial. 5b4 is a factor of -25a2b5 and -35b4, but not a3. Additionally, a2 is a factor of a3 and -25a2b5, but not -35b4. 1 is the GCF of the coefficients. There are no common variables among all three terms of the polynomial.  5b4 is the GCF of –25a2b5 and –35b4, but not a3.  a2 is a factor of a3 and – 25a2b5, but not –35b4.

Considering the multiplciation of the GCF of the numeric terms and of the variables, the GCF of the polynomial is of 1, hence he is not correct.

What is the greatest common factor of a polynomial?

It is the multiplication of the GCF of the numeric constants by the GCF of the coefficients.

In this problem:

  • The coefficients of a are 3, 2 and 0, hence the GCF is a^0.
  • The coefficients of b are 0, 5 and 4, hence the GCF is b^0.
  • As for the numeric term, the terms are 1, 25 and 35, hence the GCF is 1.

Thus:

a^0 * b^0 * 1 = 1

As Isaiah did not take into account the coefficients that are zero, his calculation is not correct.

More can be learned about the greatest common factor at brainly.com/question/6032811

Which is the longest 2 km 25m 2500 cm or 3000 mm

Answers

2km=2 kilometer
kilo=1000 so 2 km=2000m

25m

2500cm
cm=centimeter=1/100 of a meter
so
2500cm=25m


mm=milimeter=1/1000 meter
so
3000mm=3m

so the longets is obviously 2000m or 2km
So,

Let's state everything in terms of meters (m).

The conversion factor between km and m is as follows:
1 km = 1000 m
Therefore, 2 km is 2000 m.

The conversion factor between cm and m is as follows:
100 cm = 1 m
Therefore, 2500 cm is 25 m.

The conversion factor between mm and m is as follows:
1000 mm = 1 m
Therefore, 3000 mm is 3 m.

Here are all the numbers in meters.
2000 m, 25 m, 25 m, 3 m

We can quickly see that 2000 m is the longest distance.  It is 2 km.

What is the average of four tenths and five thousandths?

Answers

four tenths is expressed as .4 
five thousandths is expressed as .005
the sum of these is .405 and divided by 2 (there are two numbers we added), we get .2025, that is the average
((4)/(10)+(5)/(1000)):2 = ((400)/(1000)+(5)/(1000))*(1)/(2) =\n \n=(405)/(1000)*(1)/(2)=(405)/(2000)=(81)/(400)= .2025


(5a^2 - b^2) - (4a^2 + 3b^2) - (a^2 - 7b^2)

Answers

answer:

3b²

step-by-step explanation:

(5a² - b²) - (4a² + 3b²) - (a² - 7b²)

= 5a² - b² - 4a² - 3b² - a² + 7b²

  • combine like terms

= 3b²

(5a^2 - b^2) - (4a^2 + 3b^2) - (a^2 - 7b^2)=\n 5a^2-b^2-4a^2-3b^2-a^2+7b^2=\n 3b^2

Which is a solution to the equation?(x −2)(x + 5) = 18

x = −10
x = −7
x = −4
x = −2

Answers

If you would like to know the solution to the equation (x - 2) * (x + 5) = 18, you can calculate this using the following steps:

(x - 2) * (x + 5) = 18
x^2 + 5x - 2x - 10 = 18
x^2 + 3x - 28 = 0
(x + 7) * (x - 4) = 0
1. x = - 7
2. x = 4

The correct result would be x = - 7.

The solutions to the equation are x = - 7 and x = 4

What are equation solutions?

Equation solutions are the true values of x in the equation

The equation is given as:

(x - 2)(x + 5) = 18

Expand the equation

x^2 + 5x - 2x - 10 = 18

Subtract 18 from both sides

x^2 + 3x - 28 = 0

Factorize the expression

(x + 7) * (x - 4) = 0

Solve for x

x = - 7 and x = 4

Hence, the solutions to the equation are x = - 7 and x = 4

Read more about quadratic equations at:

brainly.com/question/8649555

Brainliest please get right

Answers

Answer:

12x-9

Step-by-step explanation:

hope this helpssss

Answer:

12x + -9 or 12x-9

Step-by-step explanation:

9x-4+3x-5

Combine the like terms.

9x + 3x = 12x

-4 - 5 = -9

12x-9